2019
DOI: 10.4314/as.v18i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and profitability analysis of catfish production: a case study of Nsukka Local Government Area of Enugu State, Nigeria

Abstract: This study examined the economics of catfish production in Nigeria using Nsukka Local Government Area of Enugu State, Nigeria as a case study. To achieve the study objectives, 40 catfish producers were randomly sampled and data for the study were collected with the aid of questionnaires. Descriptive statistics and net farm income analysis were employed for the analysis of the data collected. The study findings show that most (85%) of the catfish farmers were males, and majority of them are in their active ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 12 publications
7
15
1
Order By: Relevance
“…This result disagrees with the findings of (Onyekuru et al, 2019) who reported that the majority (75%) of fish farmers had below 5 years of experience. (Oluwasola and Ige, 2015) opined that fish farming experience is a desirable for increased profitability in fish production.…”
Section: Okoh Et Al 2021 Ojas 2(2) |4contrasting
confidence: 99%
See 1 more Smart Citation
“…This result disagrees with the findings of (Onyekuru et al, 2019) who reported that the majority (75%) of fish farmers had below 5 years of experience. (Oluwasola and Ige, 2015) opined that fish farming experience is a desirable for increased profitability in fish production.…”
Section: Okoh Et Al 2021 Ojas 2(2) |4contrasting
confidence: 99%
“…In the short run, these costs include both variable and fixed costs of production. The variable costs, involved in catfish production as shown in Table 2, include catfish seeds (fingerlings), catfish feeds, labour, petrol, transportation and miscellaneous costs (Ugwumba and Chukwuji, 2010;Ochiaka and Obasi, 2019;and Onyekuru et al, 2019). The average value of fixed cost is presented in Table 3.…”
Section: Gross Margin Analysismentioning
confidence: 99%
“…The coefficient of membership of cooperative society (X 5 ) was positive and statistically significant at 5 % implying that being a member of cooperative society will substantially enhance fish production. This agrees with Okike (2000) and Onyekuru et al (2019) who reported that farmers who belong to cooperative society have access to good quality inputs, information, organised marketing of production and increased business performance (output) than those who do not belong to a society.…”
Section: Socioeconomic Determinants Of Fish Productionsupporting
confidence: 89%
“…For instance, Omeje, Sule and Aguihe (2020) opined that aqua-culturists within the economically active age possess the potentials to expand for higher income. Onyekuru, Ihemezie and Chima (2019) gave an insightful thought that fish farmers with longer years of experience are expected to be more productive than those with shorter years of experience; while Adeosun et al (2019) reported that the years of experience in fish farming and number of ponds per farmer were positive determinants of net farm income. On this note, Zacharia et al (2013) opined that understanding these factors is important in policy formulation in aquaculture sub-sector as it allows refining management strategies to reflect the needs and aspirations of the people concerned.…”
Section: Introductionmentioning
confidence: 99%